Weakly Compatible Mappings Along With Property E.A. In Fuzzy Metric Space And Common Fixed Point Theorem - S.K.Jain; Raj Singh Chandelkar; Shoyeb Ali Sayyed (International Journal of Scientific Research and Innovative Studies, 2022)
The present review article is an enhancement of a common fixed point theorem in fuzzy metric space for a pair of weakly compatible mappings along with property E.A. . In this article we have extended, established and improved result with the help of a contractive type condition and altering distance function . KEYWORDS : Altering Distance, E.A. Property, Fixed Point Theorem, Fuzzy Metric Space , Weakly Compatible